Improving Climate Risk Management at Local Level – Techniques, Case Studies, Good Practices and Guidelines for World Meteorological Organization Members - Martínez, R.; Hemming, D.; Malone, L.; Bermudez, N.; Cockfield, G.; Diongue, A.; Hansen, J.; Hildebrand, A.; Ingram, K.; Jakeman, G.; Kadi, M.; McGregor, G. R.; et al. (IntechOpen, 2012)
None